Politik Deliberatif dalam Musyawarah Perencanaan Pembangunan: Analisis Structures and Meanings Atas PP RI No. 28/2008 - Muzaqqi, Fahrul (Jurnal Konstitusi, 2013)
The atmosphere of Indonesian democratic decentralization presents an interesting phenomenon about the strength of demand at the local level participation. Participation was on its way, legally enshrined in both the legal basis, namely PP RI No. 8 Year 2008 about stage, preparation procedures, control and evaluation of Regional Development Plan (in legal terminology known as Musrenbang). That's where the participation is so arranged that it gains the spirit of development planning in local areas level with the hope that it will combine top-down and bottom-up approaches. This study focuses on efforts to analyze the two legal basis from the perspective of theory and practice of deliberative democracy in which participation based on inter-subjective communication is at the heart of modern democratic state.In search of the analysis, the findings are somewhat surprising. Those are that in Musrenbang, the nuance was still top-down so that they are not worthy to be equated with the theory and practice of deliberative democracy. That top-down shade includes the initial planning, control and evaluation of which are still very elitist. In terms of the arrangement of initial planning for development either RPJPD, RPJMD or RKPD is conducted by the Regional Development Planning Agency. In terms of control, officials from the home affairs ministry level to regent/mayor including Bappeda are involved. In all the stages, the people are involved but only to give input. While in the case of the evaluation, the greatest authority remains in the hands of the relevant authorities at every level of government. People have the chance to evaluate only as far as they have accurate information. In other words, people will find it hard to participate and evaluate the planning that has been done since the standard of accuracy of the information is still determined by the government.As a result, using the structures and meanings analysis, this thesis research confirms that the standards of deliberative democracy need to thrust into the legal basis governing participation in development planning so that decisions resulting in better planning could reflect the aspirations of the people. However, democracy is essentially regierung der regierten (rule of those who governed).